Efficient Preparation Process for TiO2 Through-Hole Membranes with Ordered Hole Arrangements. Issue 14 (1st January 2018) - Yanagishita, Takashi; Inada, Hiromi; Kondo, Toshiaki; Nguyen, Nhat Truong; Schmuki, Patrik; Masuda, Hideki
Abstract : Ordered TiO2 through-hole membranes were obtained effectively by the repeated use of a Ti substrate with ordered concaves. A combined process involving the formation of two-layer structures with different solubilities through an intermediate heat-treatment, and selective dissolution of the bottom part of the oxide allows the repeated use of the Ti substrate with an ordered array of concaves, which act as initiation sites for hole development during the subsequent anodization. For the repeated use of the Ti substrate with ordered concaves, the oxide layer must be removed selectively without the dissolution of the Ti substrate. A mixed solution of HF and CrO3 was found to be effective for selective dissolution. Ordered TiO2 through-hole membranes obtained by this process can be used in various applications requiring an ordered hole arrangement.